New pull-out capacity equations for the design of screw fastener connections in steel cladding systems - Sivapathasundaram, Mayooran; Mahendran, Mahen (Thin-walled structures, 2018)
In recent times, the roofing systems made of thin and high strength steel roof sheeting and battens or purlins are predominantly used in the construction of low-rise buildings. However, such thin steel roofing systems continue to fail frequently at their screw fastener connections during high wind events such as storms and cyclones due to inadequate connection capacities. Localised pull-out failures occurring at the thin steel roof sheeting to batten or purlin connections have been the root cause for extensive loss of roofing systems under high wind uplift loads over many years. Such premature connection failures often cause partial or even complete loss of steel roofing systems and, thus allowing rainwater to cause severe damage to building contents. Therefore a detailed experimental study was conducted to investigate the pull-out failures occurring at the steel roof sheeting to batten or purlin connections. One hundred and eighty-seven small scale pull-out tests were conducted for this purpose using a range of screw fastener sizes and many thicknesses of thin steel roof battens and purlins. This paper presents the details of this experimental study and the pull-out capacity data obtained from the tests. It then presents suitable design equations and capacity reduction factors to accurately determine the pull-out capacities of screw fastener connections commonly used in steel roofing systems. In the development of design equations, 592 pull-out capacity data obtained from another experimental study at the Queensland University of Technology were also used. The new design equations can also be used for the screw fastener connections in steel wall cladding systems subject to high wind suction loads. •Conducted a detailed experimental study to investigate the pull-out failures in thin steel cladding systems.•Identified the critical parameters that influence the pull-out failure loads of screw connections.•Used theoretical understanding to identify the other critical parameters.•Demonstrated the inadequacy of current design equations in cold-formed steel design standards.•Developed new pull-out capacity equations for the design of screw connections in steel cladding systems.